Possibilities and Limitations in Current Translational Stem Cell Research - Kitala, Diana (Biochemistry, 2023)
Although the concept of using advanced therapy products such as stem cells seems to be a key strategy in the treatment of various diseases, much information in this area remains unknown. Stem cell products are highly complex, much more complex than chemical-based drugs. More and more often there are data indicating the risk of using stem cells. These risks are determined by various factors that are related to quality, biological activity, and the use itself, and thus administration. Therefore, it is very important to constantly systematize knowledge in this area. This book was created to present both the perspective of basic research, including the manipulation and changes in the properties of cells, and the changes and novelties in therapies themselves.